Peningkatan Keaktifan dan Hasil Belajar IPA Melalui Strategi Team Games Tournament (TGT) Siswa Kelas VB SD Muhammadiyah 10 Tipes Surakarta Tahun Ajaran 2015/2016 - Sholeh Prasetya, Dhimas, Dra. Risminawati,M.Pd (2016)
This classroom action research aims (1) To increase the activity of learning science memalui strategy Team Games Tournamen (TGT) in Class VB in SD Muhammadiyah 10 Tipes Surakarta (2) To improve learning outcomes IPA through a strategy of Team Games Tournamen (TGT) graders VB in SD Muhammadiyah 10 Tipes. The research subject of this class action is the class VB SD Muhammadiyah 10 Tipes totaling 33 students. Data collection using interviews, observation, testing, and documentation. In testing the validity of the data used triangulation and source triangulation techniques. Data were analyzed using interactive analysis include: data reduction, peyajian data, and drawing conclusions. The results of the research that has been done, the increased activity of learning that is at the pre-cycle 29.54% (10 students), the first cycle of 50% (16 students), and the second cycle 79.54% (27 students). Improved student learning outcomes in pre-cycle to 33.33% (11 students), the first cycle of 48.48 (16 students), and the second cycle 72.72% (24 students). It is concluded that Team Games Tournament strategy can enhance the activity and student learning outcomes VB class 10 Tipes SD Muhammadiyah Surakarta. Keywords: Strategy Team Games Tournament, liveliness, and learning outcomes